Sumber Hukum Islam (Dalil Syari): Dalil yang Disepakati - Besse Ruhaya; Artikaa Putri; Athirah Sulaiman; Muh. Adam Sudarta (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Islamic law serves as a comprehensive guide for Muslims, derived from the divine revelation of Allah SWT, and regulates various aspects of human life, including the relationship between humans and God as well as interactions among individuals. This study aims to examine the agreed-upon sources of Islamic law (dalil syar'i) recognized by the majority of Islamic scholars, namely the Qur'an, Sunnah, Ijma' (consensus), and Qiyas (analogical reasoning), along with their positions, functions, and roles in the process of istinbath al-ahkam (legal deduction). This research employs a library research method using a descriptive qualitative approach through the analysis of relevant literature on ushul al-fiqh and the sources of Islamic law. The findings indicate that the Qur'an is the primary and highest source of Islamic law, serving as the foundation of all legal rulings. The Sunnah functions as an explanation, elaboration, and complement to the Qur'an. Ijma' provides a legal basis through the consensus of qualified Muslim jurists on issues not explicitly addressed in the primary texts, while Qiyas serves as a method of analogical reasoning to determine legal rulings for new issues based on a shared effective cause ('illah) with existing cases. These four sources complement one another in establishing a systematic, comprehensive, and adaptable Islamic legal system capable of addressing contemporary issues while remaining consistent with the principles of Islamic law.